Antitrust in Data Driven Markets & Legal Framework for Influencers, Native Advertising and Control over the Use of AI in Marketing - Kilpatrick, Bruce; Kobel, Pierre; Këllezi, Pranvera (LIDC Contributions on Antitrust Law, Intellectual Property and Unfair Competition, 2023)
XVII, 457 p. 1 illus.